2018
DOI: 10.1007/978-3-319-94749-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Making the Right Decision: Justice in the Asylum Bureaucracy in Norway

Abstract: This chapter is based on the doctoral dissertation, 'The burdens of discretion. Managing uncertainty in the asylum bureaucracy' (Liodden 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
3
0
6
Order By: Relevance
“…Mitt doktorgradsprosjekt i sosiologi handlet om hvordan saksbehandlere i Utlendingsdirektoratet (UDI) avgjør hvem som anerkjennes som flyktning (Liodden, 2017). Datamaterialet i prosjektet besto av intervjuer med saksbehandlere, dokumenter i et utvalg asylsaker og observasjoner av asylsaker i retten.…”
Section: Vurdering Av Asylsaker I Udiunclassified
“…Mitt doktorgradsprosjekt i sosiologi handlet om hvordan saksbehandlere i Utlendingsdirektoratet (UDI) avgjør hvem som anerkjennes som flyktning (Liodden, 2017). Datamaterialet i prosjektet besto av intervjuer med saksbehandlere, dokumenter i et utvalg asylsaker og observasjoner av asylsaker i retten.…”
Section: Vurdering Av Asylsaker I Udiunclassified
“…Mitt doktorgradsprosjekt i sosiologi handlet om hvordan saksbehandlere i Utlendingsdirektoratet (UDI) avgjør hvem som anerkjennes som flyktning (Liodden, 2017). Datamaterialet i prosjektet besto av intervjuer med saksbehandlere, dokumenter i et utvalg asylsaker og observasjoner av asylsaker i retten.…”
Section: Vurdering Av Asylsaker I Udiunclassified
“…A way out of this dilemma for decision-makers has been to value "asylum while devaluing those who claim it" (Fassin & Kobelinsky, 2012, p. 274), which assumes that the fewer people who are granted asylum, the more protected the Refugee Convention. Other researchers have concluded that decision-makers solve this dilemma by referring to procedural matters as a way to signify justice in the absence of certainty (Johannesson, 2017;Affolter, Miaz & Poertner, 2019;Liodden, 2019).…”
Section: Contested Assumptions Underpinning Credibility Assessmentsmentioning
confidence: 99%